Persepsi Masyarakat Terhadap Realisasi Kepemimpinan Kepala Desa Perempuan Di Desa Tellongeng Kecamatan Mare Kabupaten Bone - Mr. Wahyudi (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
This study aims to determine the community's perception of the realization of the leadership of the female village head in Tellongeng Village, Mare District, Bone Regency. This study uses a type of quantitative research with descriptive analysis explanation. Data collection techniques were obtained by distributing questionnaires to 96 respondents from 2,609 populations with a 90% confidence level and 10% error. Data analysis techniques using IBM SPSS Statistics. The results showed that the people of Tellongeng Village, Mare District, Bone Regency had a positive perception of the leadership of the female village head in Tellongeng Village, Mare District, Bone Regency. The community's assessment of the female village head is in the good classification, the realization of leadership shows the ability of the female village head in planning, the ability to lead, and the ability to control or oversee the people she leads is in the fairly good category.